THE LEGISLATIVE AND JUDICIAL OMISSION OF LINGUISTIC RIGHTS OF INDIGENOUS PEOPLES IN VENEZUELA AND ECUADOR: THE LEGISLATIVE AND JUDICIAL OMISSION OF LINGUISTIC RIGHTS OF INDIGENOUS PEOPLES IN VENEZUELA AND ECUADOR - Mendoza Escalante, Pablo Ricardo (2020)
This work analyzes the legal framework of cultural rights to the use of ancestral languages in Ecuador and Venezuela. Through bibliographic research it exposes the current norms on indigenous linguistic rights in the face of their possible violation. It verifies that, in different areas of justice, the structure and worldview of the original languages is not understood. It proposes the formulation of new public policies in justice systems, from an intercultural perspective as the central axis. Presents the intercultural proposal of the Legal Observatory of the University of Otavalo.